2014
DOI: 10.5901/mjss.2014.v5n23p435
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Robustness of Okun’s Law in South Africa: An Error Correction Modelling approach

Abstract: Key intension of this paper was to verify Okun's law in the South

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
4
1
Order By: Relevance
“…The study up held the findings of the relationship to be negative (Geldenhuys, 2007). The finding ran contrary to the findings that Okun's law is not applicable in South Africa (Moroke, 2014). This study found evidence of the superiority of the Dynamic version over the Difference version.…”
Section: Discussion Of Findings and Conclusioncontrasting
confidence: 99%
“…The study up held the findings of the relationship to be negative (Geldenhuys, 2007). The finding ran contrary to the findings that Okun's law is not applicable in South Africa (Moroke, 2014). This study found evidence of the superiority of the Dynamic version over the Difference version.…”
Section: Discussion Of Findings and Conclusioncontrasting
confidence: 99%
“…Firstly, we found the expected negative and significant long-run as well as insignificant short-run estimates on the GDP variable for all four classes of unemployment. Clearly this finding corresponds to Okun's law which previous empirical supporting evidence for this relationship has been provided by Geldenhuys and Marnikov (2007) and Phiri (2014) but differs from the findings obtained in Moroke et al (2014) and Banda et al (2016).…”
Section: Macroeconomic Variables As Determinants Of Unemploymentsupporting
confidence: 67%
“…One of the oldest theories linking unemployment with economic activity is Okun's (1962) law, which assumes a negative relationship between unemployment and economic output. Notably this relationship has received much empirical support in industrialized economies such as the United States (Grant, 2018;Guisinger, Hernandez-Murillo, Owyang, Sinclair, 2018), Spain (Porras-Arena, Martin-Roman, 2019), OECD countries (de Mendonca, de Oliveira, 2019) and yet has received very little empirical support for the South African economy (see Moroke, Leballo, Mello, 2014;Banda, Ngirande, Hogwe, 2016). Another popular theory describing the dynamics of unemployment across the steady-state comes courtesy of the Phillips curve which assumes an inverse relationship between inflation and unemployment.…”
Section: Fiscal Monetary and Macroeconomic Determinants Of Unemployment As Dictated By Literaturementioning
confidence: 99%
“…Geldenhuys and Marinkov (2007) found that unemployment is inversely related to output in the South African economy over the 1970 to 2005 period and there was evidence of asymmetry in the Okun's relationship. But, Moroke, Leballo and Mello (2014) explored the relationship between unemployment and economic growth of South Africa from 1990Q1 to 2013Q4. The study showed that Okun's coefficient did not conform to the expected sign; thus, affirming that Okun's law is irrelevant in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%